Exploring Midwives’ Roles on Managing Perinatal Mental Health: Insights into Scientific Perspective on Care Practices and Psychosocial Support - Rizka Adela Fatsena; Niken Bayu Argaheni; Anis Laela Megasari (Postgraduate, University of Mataram, 2024)
Perinatal Mental Health is prominent for the well-being of the mother and child, so consideration provides effective support and care for women in the perinatal period given by Midwives can be helped. The study aimed to synthesize primary research on midwives’ experiences of caring for women who experience perinatal mental health and well-being. Using mixed methods systematically combined with quantitative and qualitative studies. This study analys was searched on three databases, ProQuest, Pubmed, and ScienceDirect, from 2021 to 2024. The population in this study were midwives who experienced PMH in the care of pregnant. Critical Appraisal Skills Programs (CASP) were used to determine the study’s methodological quality. By contrast, the synthesis method uses the modified PEOS method. Data extraction, quality assessment, and thematic analysis were conducted using PRISMA-P guidelines. 2926 records were returned, with 10 articles meeting inclusion criteria. Participants included midwives. The findings indicate that there is a need for a sustainable development program for midwives to increase knowledge, attitudes, communication, collaboration, and assessment skills for pregnant women who experience PMH by a scientific perspective. All maternity services must provide specific services to assess and identify Perinatal Mental Health problems. Indeed, the emotional well-being of pregnant women is the goal of debriefing midwives.